Environmental labeling of building sustainability: Focus on international certifications - TEBBOUCHE, Hocine; BOUCHAIR, Ammar; Blibli, Mustapha (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2023)
The environmental labelling of sustainable buildings has become a major concern for the architectural design. Numerous building sustainability assessment methods were developed in various countries, namely the British BREEAM, the American LEED, the German DGNB, the French HQE and the United Arab Emirates ESTIDAMA. The present study aims to find the most appropriate approach that suits the Algerian context. A comparative study is conducted using an analytical procedure. The study focuses on the objectives, the evaluation procedures, the assets, and the qualitative assessment indicators for the environmental performance of the buildings. As a result, HQE of France and ESTIDAMA of the United Arab Emirates appeared to be best suited to the Algerian context.